Relation between human resource development climate and organisational commitment: empirical study in Indian banking sector. (2016) - Mittal, Shweta; Gupta, Vishal; Motiani, Manoj
The present study examines the relationship between the three subsets of HRD climate i.e., HRD mechanisms, general climate and OCTAPAC with the organisational commitment in the Indian banking sector. Data was collected using a survey questionnaire from 203 bank employees working in the public and private Indian banks. Data analysis was performed using structural equation modelling and study found that there is a positive relationship between HRD mechanisms, general climate and OCTAPAC with organisational commitment. So, the organisations which have a favourable HRD climate are more committed in their organisation. Implications for research and practice are discussed.